A Comparison of Red Fluorescent Proteins to Model DNA Vaccine Expression by Whole Animal In Vivo Imaging - Kinnear,E; Caproni,LJ; Tregoning,JS (PLOS One, 2015)
DNA vaccines can be manufactured cheaply, easily and rapidly and have performed well inpre-clinical animal studies. However, clinical trials have so far been disappointing, failing toevoke a strong immune response, possibly due to poor antigen expression. To improveantigen expression, improved technology to monitor DNA vaccine transfection efficiency isrequired. In the current study, we compared plasmid encoded tdTomato, mCherry,Katushka, tdKatushka2 and luciferase as reporter proteins for whole animal in vivo imaging.The intramuscular, subcutaneous and tattooing routes were compared and electroporationwas used to enhance expression. We observed that overall, fluorescent proteins were not agood tool to assess expression from DNA plasmids, with a highly heterogeneous responsebetween animals. Of the proteins used, intramuscular delivery of DNA encoding either tdTomatoor luciferase gave the clearest signal, with some Katushka and tdKatushka2 signalobserved. Subcutaneous delivery was weakly visible and nothing was observed followingDNA tattooing. DNA encoding haemagglutinin was used to determine whether immuneresponses mirrored visible expression levels. A protective immune response against H1N1influenza was induced by all routes, even after a single dose of DNA, though qualitative differenceswere observed, with tattooing leading to high antibody responses and subcutaneousDNA leading to high CD8 responses. We conclude that of the reporter proteins used,expression from DNA plasmids can best be assessed using tdTomato or luciferase. But, thedisconnect between visible expression level and immunogenicity suggests that in vivowhole animal imaging of fluorescent proteins has limited utility for predicting DNA vaccineefficacy.